ACADEMIC MOBILITY POLICIES IN HIGHER EDUCATION OF BOSNIA AND HERZEGOVINA - Daniela POPA; Ratko KNEZEVIC (National Centre for Policy and Evaluation in Education, 2018)
Teaching and studying abroad are the key elements in reducing regional isolation of academic community. International exchanges programmes are particularly important for their personal and professional development and have positive effects for the socio-economic area as well. Mobility allows every candidate to gain an invaluable, new experience, to learn foreign languages and to develop interpersonal skills in culturally diverse environments. This article provides a SWOT analysis of the implementation of education policies regarding academic mobility in higher education institutions in Bosnia and Herzegovina. The research is a qualitative one. The collecting data methods used were semi-structured interviews with key respondents and experts in Higher Education and study of documents (laws, implementation measures, decisions of university administration councils). The results show that some of the most valuable advantages are: border-crossing knowledge transfer, the increased number of young professionals having better chances of employment. The main barriers are the attitudes inherited from former education system and insufficiency in advertising of all benefits they can gain from mobility. The value of the article is in its potential to emphasize the complexity of the country having unusually lots of ministries of education that affect academic mobilities.